Starvation Alters the Apparent Half-Saturation Constant for Methane in the Type II Methanotroph Methylocystis Strain LR1 - Dunfield, Peter F. (American Society for Microbiology, 2000)
When cells of a type II methanotrophic bacterium (Methylocystis strain LR1) were starved of methane, both the K(m(app)) and the V(max(app)) for methane decreased. The specific affinity (a(o)(s)) remained nearly constant. Therefore, the decreased K(m(app)) in starved cells was probably not an adjustment to better utilize low-methane concentrations.